A Collaborative Approach: Care Staff and Families Working Together to Safeguard the Quality of Life of Residents Living With Advanced Dementia. (May 2019) - Hughes, Sian Ellen; Woods, Bob; Algar-Skaife, Katherine; Jelley, Hannah; Jones, Catrin Hedd
Objectives: This study aimed to explore the quality of life and well-being of care home residents living with advanced dementia, how personalised care can be achieved where the person is completely dependent on others for care and how individuals' choices and human rights were upheld. Methods: The study design used a qualitative approach, with data collected through in-depth, semi-structured interviews with 8 family members, all of whom visited daily, and 8 care staff. Results: Emerging themes highlighted the importance of family involvement, signs of well-being, communication and the valued role of direct care staff. Discussion: Participants were able to identify factors of residents' well-being in residents living with advanced dementia. Family members who visited daily saw themselves working collaboratively with care staff to maintain the quality of life of their relatives and engage in proxy decision making. Regarding human rights, the emphasis was on avoiding abuse, rather than promoting well-being.